2019
DOI: 10.2147/copd.s184695
|View full text |Cite
|
Sign up to set email alerts
|

<p>COPD classification models and mortality prediction capacity</p>

Abstract: ObjectiveOur aim was to assess the impact of comorbidities on existing COPD prognosis scores.Patients and methodsA total of 543 patients with COPD (FEV1 <80% and FEV1/FVC <70%) were included between January 2003 and January 2004. Patients were stable for at least 6 weeks before inclusion and were followed for 5 years without any intervention by the research team. Comorbidities and causes of death were established from medical reports or information from primary care medical records. The GOLD system and the bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 36 publications
(60 reference statements)
2
13
0
4
Order By: Relevance
“…All these classifications were initially designed not to assess prognosis, but to aid clinicians in creating optimal treatment regimens for patients. Thus, the prognostic ability of GOLD 2019 compared to previous classifications is largely unknown, with only a few published studies [ 11 , 12 ]. To address this issue, we used pooled data from 17 139 patients of 22 COPD cohorts and 11 countries and compared the prognostic capacity of the 2019 versus 2015 GOLD staging classifications to predict mortality.…”
Section: Introductionmentioning
confidence: 99%
“…All these classifications were initially designed not to assess prognosis, but to aid clinicians in creating optimal treatment regimens for patients. Thus, the prognostic ability of GOLD 2019 compared to previous classifications is largely unknown, with only a few published studies [ 11 , 12 ]. To address this issue, we used pooled data from 17 139 patients of 22 COPD cohorts and 11 countries and compared the prognostic capacity of the 2019 versus 2015 GOLD staging classifications to predict mortality.…”
Section: Introductionmentioning
confidence: 99%
“…In our opinion, it is probably a matter of people's expectations changing as they get older and/or they progressively get used to living with the disease. It might be expected that cardiovascular comorbidities would play an important role in HRQoL of COPD patients [39], but this does not seem to be observed, unlike for other comorbidities, such as depression, which have been shown to contribute strongly to HRQoL [40]. In a European cross-sectional study, a cut-off of three comorbidities established significant differences in HRQoL, and though COPD patients with cardiovascular comorbidities had worse scores in HRQoL (SGRQ), the minimal clinically important difference was not reached [41].…”
Section: Discussionmentioning
confidence: 99%
“…Although comorbidities are increasingly identified as important factors of COPD management and outcomes [ 15 ], studies specifically designed to evaluate the relationships between comorbidities and long-term outcomes in subjects with a diagnosis of COPD admitted to an internal medicine ward are scarce [ 16 ], and this is also true for several chronic diseases [ 17 ]. A recent study showed that the addition of comorbidities to age, BMI, blood markers and indexes such as smoking status, dyspnea assessment, airway obstruction produced a model, known as BARC index, that performed better than established index scores in predicting 1-year mortality [ 18 ].…”
Section: Discussionmentioning
confidence: 99%